END-TO-END QUALITY OF SERVICE SUPPORT OVER UMTS - CHE BAHARUN, MIOR RIDZUAN BIN (Universiti Teknologi PETRONAS, 2012)
End-to-end quality of service are very crucial in determine the quality of a certain network and can be seeing as a successful factor for every mobile network. This paper will discuss the end-to-end quality of service support over UMTS via DiffServ paradigm in achieving the end satisfactory for the customer. Telecommunications industries nowadays are rapidly growing from generation to generation advancement being making by the service provider. In order to tackle every customer, service provider will find a way to enhance their end-to-end quality of service over UMTS to satisfy their customer. In this paper, research for characteristic for UMTS network and DiffServ paradigm have been made in order to understand every criteria for achieving the best end-to-end quality of services for this UMTS network via DiffServ method. Mapping between DiffServ and UMTS network will be simulated and evaluated in OPNET software. Many scenarios will be simulated and will be compared in order to find the best result when using this DiffServ paradigm. Every result from each scenario will be shown in a graph which will be easier to see the differences between the variations of the end delay times for each scenarios mapping. As a solution, from the variations of the end delay time, it shows that DiffServ paradigm give a lower delay time and this means that end-to-end quality of services support over UMTS network via DiffServ paradigm can give the satisfactory services for the end user. In the future, as the advancement keep growing for UMTS network, others research can be done to find another paradigm that can give more end-to-end quality of services satisfactory for end users.